Seismic response and interaction of complex soil retaining systems - Kontoe,S; Zdravkovic,L; Menkiti,CO; Potts,DM (Computers and Geotechnics, 2012)
This paper examines the seismic response of a large and complex system comprising a Lock chamber and three neighbouring water saving basins (WSBs). The developed two-dimensional plane strain finite element model included the entire system in order to explore the interaction of the various structures. The first set of analyses was undertaken under static conditions to simulate the construction sequence and to establish the stress regime prior to the examined seismic event. Subsequently, dynamic time domain analyses were performed to examine the response of the system to seismic loading. The ground motion was applied into the finite element mesh employing a sub-structuring technique which enables economic modelling of large computation domains and accurate representation of the semi-infinite half-space. The paper explores some aspects of the numerical modelling of such complex systems, such as the impact on the predicted seismic response of the adopted constitutive model and the modelling of hydrodynamic effects. The discussion of the dynamic analyses results focuses on the main Lock structure, looking at the prevailing modes of deformation, the potential lift-off of the base of the Lock walls and the interaction of the main wall with the other retaining structures.